2002
DOI: 10.1023/a:1020118425588
|View full text |Cite
|
Sign up to set email alerts
|

Nightmares as a coping mechanism for stress.

Abstract: The cause of nightmares remains unclear. However, previous research suggests that stress may playa key role and that nightmares may actually serve a beneficial function. Thus, the purpose of this study was to examine the overall relationship between these two variables and assess the hypothesis that nightmares serve as a coping mechanismfor stress. To accomplish these goals, a group of 412 psychology students were separated into low, medium, and high nightmare frequency groups as well as low, medium, and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 46 publications
2
23
0
1
Order By: Relevance
“…In line with an earlier study on NM participants (Nielsen et al, 2010), our NM group was characterized by an enhanced first-night effect. Levin and Nielsen's (2007) neurocognitive model explained this phenomenon by claiming that the discomfort and inconvenience of the sleep laboratory setting affect the NM group more due to their higher stress reactivity (Cernovsky, 1984;Coalson, 1995;Cook, Caplan, & Wolowitz, 1990;Hartmann, 1984;Picchioni et al, 2002). Our results are controversial in supporting this claim.…”
Section: Discussionmentioning
confidence: 74%
“…In line with an earlier study on NM participants (Nielsen et al, 2010), our NM group was characterized by an enhanced first-night effect. Levin and Nielsen's (2007) neurocognitive model explained this phenomenon by claiming that the discomfort and inconvenience of the sleep laboratory setting affect the NM group more due to their higher stress reactivity (Cernovsky, 1984;Coalson, 1995;Cook, Caplan, & Wolowitz, 1990;Hartmann, 1984;Picchioni et al, 2002). Our results are controversial in supporting this claim.…”
Section: Discussionmentioning
confidence: 74%
“…Picchioni et al. () found that nightmares were related not only to stress, but also to elevated attempts at coping with stressful events (during the day). Thus, the authors concluded that nightmares might represent night‐time attempts at coping and might in fact help alleviate stress.…”
Section: Relationship Of Dreaming and Psychological Distress In Adultsmentioning
confidence: 99%
“…On the other hand, some studies found that psychological distress predicted an increase in unique dreaming patterns, but not vice versa (e.g., Soffer‐Dudek & Shahar, ), suggesting that dreaming might be a consequence of emotional changes. In addition, some forms of dreaming, such as nightmares, might be related to attempts at coping with emotional distress (e.g., Hartmann, ; Picchioni et al., ). If this is true, we would expect early dreaming patterns to predict a decrease in psychopathology.…”
Section: Dream Patterns and Psychological Problems In Childhood And Amentioning
confidence: 99%
“…In contrast, it has also been suggested that nightmares themselves might be the adaptive process. For example, Picchioni and colleagues46 reported that nightmares are positively associated with waking attempts to cope with stress, suggesting that nightmares may serve a beneficial function. However, the absence of a direct assessment of successful outcome of coping in this study makes it difficult, at best, to relate nightmares to functional outcomes.…”
Section: Etiologymentioning
confidence: 99%